Synergistic effects of vagus nerve stimulation and antiseizure medication: original communication - Winter, Yaroslav; Sandner, Katharina; Glaser, Martin; Ciolac, Dumitru; Sauer, Viktoria; Ziebart, Andreas; Karakoyun, Ali; Chiosa, Vitalie; Saryyeva, Assel; Krauss, Joachim K.; Ringel, Florian Alexander; Groppa, Sergiu (Journal of neurology, 2023)
Vagus nerve stimulation (VNS) is an effective, non-pharmacological therapy for epileptic seizures. Until now, favorable combinations of different groups of antiseizure medication (ASM) and VNS have not been sufficiently addressed. The aim of this study was to identify the synergistic effects between VNS and different ASMs.
Online veröffentlicht: 27. Juni 2023
Gesehen am 17.07.2024